SERUM RELATIONSHIP 25-HYDROXY VITAMIN D [25(OH)D] WITH PRIMARY DYMENORHEA IN ADOLESCENT WOMEN IN PALEMBANG - Sepiwiryanti, Wika; Legiran; Effendi , Yusuf (Majalah Kedokteran Sriwijaya, 2023)
Primary dysmenorrhea is the most common gynecological problem in women of all ages and races with a peak prevalence occurring in the late teens or early twenties. Primary dysmenorrhea can be caused by several factors such as age, family history, body mass index, socioeconomic status, education, smoking, alcohol use, as well as the potential role of a woman's daily diet. Primary dysmenorrhea is considered to be one of the main problems in women and is a major public health cause of chronic pelvic pain and has an adverse effect on a woman's life, health and quality of life. Micronutrients including vitamins and minerals are needed to maintain the body's physiological functions. Micronutrient deficiencies can have various negative effects on human health. Vitamin D receptors are located in the human uterus and vitamin D can inhibit prostaglandin synthesis. The purpose of this study was to determine the relationship between 25-hydroxy vitamin D [25(OH)D] serum levels and the incidence of primary dysmenorrhea . This study used an analytic observational design with a case-control approach. A total of 117 respondents were involved in this study, the sample collection was conducted in April- June 2022, with a total sample size of 58 case samples and 59 control samples that met the inclusion criteria. Examination of serum 25-hydroxy vitamin D [25(OH)D] levels used the ELfA method and then the results were recorded in the observation sheet, data analysis used the chi-square statistical test. From the results of this study, it was found that the median serum 25-hydroxy vitamin D [25(OH)D] level in primary dysmenorrhea was 12.75 ng / mL lower than the control was 14.10 ng/mL The analysis of serum 25- hydroxy vitamin D [25(OH)D] levels was carried out using ROC curve analysis and the best cutoff point parameter was ≤ 10.30 ng/ mL. This study concludes that there is a significant relationship between 25-hydroxy vitamin D [25(OH)D] serum levels and the incidence of primary dysmenorrhea with a value of p = 0.001.